Revealing the diversity of ant-eating spiders in Colombia I: morphology, distribution and taxonomy of the barronus group of the genus Tenedos O. Pickard-Cambridge, 1897 (Araneae: Zodariidae) - Martínez, Leonel; Brescovit, Antonio D.; Cuervo, Luis G. Quijano (Zootaxa, 2022)
The genus Tenedos O. Pickard-Cambridge, 1897 is the most diverse among Neotropical Zodariids. It is composed of 44 species, fourteen of which occur in Brazil, while in Colombia, the diversity of the genus is poorly known, with only seven species recorded for the country. Based on genital morphology, several species groups can be distinguished within the genus, but these have not been formally established. We propose the species group barronus to include 41 species, 34 of which are distributed in Colombia and the other seven exclusively occurring in: Brazil (one Amazonian species), Peru (three Andean species), and Venezuela (three Andean species). The previously proposed species Tenedos andes Jocqué & Baert, 2002; T. peckorum Jocqué & Baert, 2002; T. jocquei Quijano & Galvis, 2018 and T. capote Jocqué & Baert, 2002 are redescribed based on the type material and the females of the two former species are described for the first time. T. barronus (Chamberlin, 1925) and T. persulcatus Jocqué & Baert, 2002 are reported for Colombia for the first time, the female of the latter is described. Twenty-eight new species are herein described, illustrated and their distributions are represented (species listed according to morphological affinities): T. ayo sp. n. (♂♀), T. calebi sp. n. (♂), T. caqueta sp. n. (♂), T. choco sp. n. (♂♀), T. cofan sp. n. (♂♀), T. dankittipakuli sp. n. (♂♀), T. eberhardi sp. n. (♂♀), T. neitai sp. n. (♂♀), T. tama sp. n. (♂♀), T. griswoldi sp. n. (♂♀), T. guacharos sp. n. (♂), T. henrardi sp. n. (♂♀), T. humboldti sp. n. (♂♀), T. carlosprietoi sp. n. (♂♀), T. narinensis sp. n. (♂), T. mesa sp. n. (♂), T. macagual sp. n. (♂♀), T. marquetones sp. n. (♂), T. medina sp. n. (♂♀) , T. pensilvania sp. n. (♂), T. piedecuesta sp. n. (♂♀), T. quipile sp. n. (♂♀), T. santarosa sp. n. (♂♀), T. luzmarinae sp. n. (♂♀), T. tatama sp. n. (♂♀), T. ticuna sp. n. (♂♀), T. wayuu sp. n. (♂) and T. yurayaco sp. n. (♂). We further provide new morphological data for some species included in the barronus group, and briefly discuss some aspects on morphological affinities and distribution between the species, based on a comparison with Tenedos type species, T. lautus O. Pickard-Cambridge, 1897. Distribution maps for all Colombian species, including new records for T. barronus and T. persulcatus, are also herein included. Additionally, an identification key for all species of the barronus group is provided.